ANALISIS BROSUR PONDOK PESANTREN DARUSSALAM BLOKAGUNG DITINJAU DARI ASPEK DESAIN GRAFIS - Hadiono, Abdi Fauji; Khasanah, Islamiatul (IAI Darussalam, 2023)
Promotion is something that must be done by an institution, promotional activities are usually carried out to introduce and inform the advantages of the institution so as to form a good image to the public, one of the promotions that is relatively used is print media in the form of brochures. Brochures contain quite a lot of messages so that readers can understand the intent to be conveyed by the promoter. Darussalam Blokagung Islamic Boarding School is one of the institutions that annually publishes brochures in the form of books and are published with different designs. Brochures play a major role as dissemination of information for guardians of students who will enroll their children in Islamic boarding schools which contain several Islamic boarding schools and school units. Messages and information on brochures will be easier to understand if they are visually appealing. The problem that will be studied in this research is to analyze the application of the graphic design aspects contained in the brochure published by Pondok Pesantren Darussalam Blokagung in 2022. The aim is to find out to what extent the brochure fulfills the graphic design aspects. The research method used is a qualitative descriptive method approach, namely by describing each subject to be studied and adjusted to a predetermined theoretical framework. After collecting data through observational research instruments, interviews and documentation, the results of the study show that PP. Darussalam Blokagung does not meet the graphic design aspects, according to Willam Lidwell et al in his book entitled Universal Principles of Design. Meanwhile, according to Ellen Lupton in her book entitled Thinking With Type, brochures have fulfilled the aspects of graphic design, because they have fulfilled the aspects of legibility, balance, unity and effective color, according to what Ellen Lupton explained. Keywords: Brochure, Design Grafis